Factors Related to Acute Respiratory Infection (ARI) in Toddlers at Radamata Health Center - Tadi, Marce Yunersi; Hinga, Indriati A. Tedju; Purnawan, Sigit (Faculty of Public Health, Nusa Cendana University, 2023)
Acute respiratory infection (ARI) is an infectious disease that is a health problem experienced by children, especially children under five because of the presence of bacteria that enter and multiply in the body until symptoms of the disease appear ranging from nose to lungs. Radamata Health Center was ranked first with the highest cases of suffering from ARI in children under five from the 16 health centers in Southwest Sumba Regency. The purpose of the study was to determine the factors associated with cases of ARI in children under five. The research method is analytic observation with a case control design approach. The research was conducted from December 2021 to January 2022 in the working area of ​​the Radamata Health Center, Southwest Sumba Regency. The sample amounted to 96 toddlers, namely there were case samples of 48 toddlers and control samples of 48 toddlers with a ratio of 1:1. The sampling technique used simple random sampling.data analysis technique used the chi-square test. The results showed that there was a relationship between LBW (p-value= 0.024, immunization (p-value= 0.041), exclusive breastfeeding (p-value= 0.007) and the presence of smokers (p-value= 0.004 while the research variable that had no relationship was nutritional status (BW/TB) (p-value= 0.608), vitamin A capsules (p-value= 0.218), preventive behavior (p-value= 0.680) with the incidence of acute respiratory infections in toddlers in the working area of the Radamata Health Center, southwest Sumba District. It is hoped that the health office and puskesmas officers will improve health promotion to the community, especially the community. in remote villages far from health care facilities